The two lies of Faven Sythe - O'Keefe, Megan E., 1985- (Orbit, 2025)
"A search for a missing person uncovers a galaxy-spanning conspiracy in this thrilling standalone space opera from award-winning author Megan E. O'Keefe. The Black Celeste is a ghost story. A once-legendary spaceship collecting dust in a cosmic graveyard known as the Clutch. Only famed pirate Bitter Amandine knows better, and she'll do anything to never go near it again. No matter the cost. Faven Sythe is crystborn, a member of the near-human species tasked with charting starpaths from station to station. She's trained to be a navigator her entire life. But when her mentor disappears, leaving behind a mysterious starpath terminating in the Clutch, she is determined to find the truth. And only Amandine has the answers. What they will find is a conspiracy bigger than either of them. Their quest for the truth will uncover secrets Amandine has long fought to keep buried - secrets about how she survived her last encounter in the Clutch, and what's really hidden out there amongst the stars..."--